From the Code Noir to Entrenched Rights - Angelo, Tony (Victoria University of Wellington Law Review, 2019)
The celebration of the service of a longstanding and much valued colleague is here taken as the opportunity to comment briefly on the employment law of Seychelles and to indicate, by reference to a few key cases, that the employment decisions reflect, perhaps unsurprisingly, significant features of contemporary Seychelles society. This article presents an historical overview of the labour law of Seychelles, followed by some case studies and a brief conclusion.